Pan-Resistome Insights into the Multidrug Resistance of Acinetobacter baumannii - Diego Lucas Neres Rodrigues; Francielly Morais-Rodrigues; Raquel Hurtado; Roselane Gonçalves dos Santos; Daniela Camargos Costa; Debmalya Barh; Preetam Ghosh; Khalid J. Alzahrani; Siomar Castro Soares; Rommel Ramos; Aristóteles Góes-Neto; Vasco Azevedo; et al. (MDPI AG, 2021)
Acinetobacter baumannii is an important Gram-negative opportunistic pathogen that is responsible for many nosocomial infections. This etiologic agent has acquired, over the years, multiple mechanisms of resistance to a wide range of antimicrobials and the ability to survive in different environments. In this context, our study aims to elucidate the resistome from the A. baumannii strains based on phylogenetic, phylogenomic, and comparative genomics analyses. In silico analysis of the complete genomes of A. baumannii strains was carried out to identify genes involved in the resistance mechanisms and the phylogenetic relationships and grouping of the strains based on the sequence type. The presence of genomic islands containing most of the resistance gene repertoire indicated high genomic plasticity, which probably enabled the acquisition of resistance genes and the formation of a robust resistome. A. baumannii displayed an open pan-genome and revealed a still constant genetic permutation among their strains. Furthermore, the resistance genes suggest a specific profile within the species throughout its evolutionary history. Moreover, the current study performed screening and characterization of the main genes present in the resistome, which can be used in applied research to develop new therapeutic methods to control this important bacterial pathogen.